دور الذكاء الاستراتيجي في تفعيل القيادة الاستراتيجية بمنظمات الاعمال /عرض تجارب رائدة - منصف, بن خديجة; سوالمية, لامية (جامعة الوادي- University of Eloued, 2017)
The aim of this study is to identify the nature, characteristics and practices of the strategic leadership, work to highlight the importance of strategic intelligence and its components. And the role of the strategic intelligencein activating thestrategic leadership. It reached a number of results, including: Presence and impact of strategic intelligence in strategic leadership, where the higher the dimensions of intelligence, the greater the effectiveness of strategic leadership. The study also recommended the necessity for the Arab and Algerian organizations to benefit from successful experiences in this field.
The role of strategic intelligence in activating strategic leadership in business organizations - Presentation of pilot experiences
مقال
Keywords: the strategic intelligencein